Factors that affect revisit intention to eco-homestay among young adults - Bee, Sin Hoey; Chee, Hao Ernn; Lean, Kai Xuan; Liew, Li Leng; Tan, Kia Kia (2020)
In an era of civilized society, the expansion of tourism has increased the requirement on accommodation, home-stay being developed. Moreover, through the changes of environment nowadays, environmentally conscious people are getting more, the development of eco-homestay was the one developed without harm to the environment. The demand for eco-homestay also increased according to the growing force of the travel industry (Clifford,2015). The sample size for this study is 200 young adults(18-34), selected as target respondents. They have been indicated as the fastest growing market segment, this is because they are open minded and have significant impact on domestic tourism and long-run growth. Furthermore, there is less study discussed about revisit intention in the field of tourism and eco-homestay. Attracting new consumers is much more expensive than retaining the existing consumers, thus revisit intention is used to evaluate the level of satisfaction of consumers, and it can help marketer save cost and create loyalty of consumers. The theory that has been applied in this study is push and pull theory. It is a common theory to understand the intention of tourists to visit the destination, the kind of experience and activities they hope to be obtained and developed (Said & Maryono, 2018). In this paper, the factors that affect the revisit intention of young adults have been identified in terms of tourist‘s characteristics, social influence, accessibility and convenience, and destination to eco-homestay. To ensure the standard and quality of questionnaire validity and reliability test have been implemented. Moreover, Statistical Package for the Social Sciences(SPSS) is the software that is executed to calculate and analyze the data which generated from the questionnaires in this research study. Inferential method applied the multiple regression to calculate R-square (R²) which was used to identify the relationship among independent variables and dependent variables in this research study. The theoretical and managerial implication has been recorded and followed by the recommendation and limitation that exist from this study which can act as guidance for future researchers.